Erratum 1 - Turcology Research Editöryel Kurul (Turcology Research)
The conflict of interest and funding statement of the article titled “An Evaluation of the Return Route of the Ten Thousand and Theches Hill: Arakli/ Sürmene– Bayburt Road” published in Turcology Research 2024 issue 79 has been changed as follows, and the information has been inadvertently forgotten to be written.Conflift of Interest: Yasin Topaloğlu, who is among the authors, is a journal editor and has not been involved in the article evaluation process. The external independent editor for this article was appointed by Atatürk University Coordinatorship of Scientific Journals. The guest editor is independent in his decision.Funding: This study was supported by TUBITAK 2519-European Union (EU) COST ACTION SEADDA 18128 Project.